STATE OF PLATELET’S AGGREGATION AND THE EFFECT OF INTERLEUKIN 4 AND 6 AT EXPERIMENTAL ALVEOLITIS - Черемісіна, В.Ф.; Березнякова, А.І. (World of Medicine and Biology, 2017)
The paper presents the results of identifying the relationship between the content of cytokines and the functional activity of platelets in rats with disturbance of the bone marrow periodontal metabolism with alveolitis. At this disease, the level of IL-4 increases, the time reaches the maximum aggregation rate at an ADP concentration of 2.5 micromol/L, and also the relationship between the degree of aggregation of platelets and the level of IL-6 at an ADP concentration of 10.0 μmol/L.
Keywords: platelet’s aggregation; interleukins; bone tissue; alveolitis